CO2 Pollution and Economic Growth: Heterogeneous Behavior for Latin America? - Riveros-Gavilanes, John Michael; Reyes-Vargas, Ana María (Sociedad y Economía, 2023)
This paper establishes an empirical approach to the relationship between pollution and economic growth by considering carbon dioxide (CO2) emissions in Latin America and their relationship with gross domestic product at constant prices. The theoretical formulation of the Kuznets environmental curve is reviewed and established with a panel of world data by region, with special emphasis on Latin American economies. The results, robust to cross-sectional dependence, indicate that increases in real economic output per capita do not lead to essential reductions in CO2 emissions per capita at the global level. This behavior is replicated at the level of regions such as Latin America and the Caribbean, Europe, Central and East Asia. It is evident that there are changes in the statistical significance of each continental region with respect to the production and controls used in the estimates.